Impact of Computational Thinking and Computer Science (CTCS) Teaching Technique at Seleceted Schools in Sarawak : A Qualitative Analysis - Nor Iqbal, Mohd Sait; Noor'ain, Aini; Kartinah, Zen (Universiti Malaysia Sabah, 2023)
Computational thinking and computer science (CTCS) is an educational approach that involves a four-stage process involving concepts of decomposition, pattern recognition, abstraction, and algorithm that promotes greater levels of thinking. Initially exclusive to computer scientists, it has further developed from the realms of computer sciences into a skill to be mastered by all levels and backgrounds of education in numerous countries. In the context of Malaysia, CTCS was incorporated into education in 2017 through the integration of elements of Information Communication Technology into almost all subjects at both primary and secondary levels. Between 2017 and 2020, the Faculty of Computer Science and Information Technology (FCSIT), UNIMAS conducted teaching certificate program for teachers, and outreach program based on digital making, programming, and robotics for students to increase their readiness in digital knowledge through computational thinking and computer science (CTCS). This paper aimed to explore the impact of the implementation of CTCS in the teaching-learning process by obtaining descriptive information through interviews with selected teachers and students. The findings showed that the reception of CT was positive as teachers found teaching easier and students showing greater interest in learning. The reception stems from CT’s ability to promote critical thinking, problem solving, and communication skills, consequently leading to greater collaborations between students and teachers.